2022
DOI: 10.1002/ceat.202200132
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Seams on the Operating Behavior of Surface Filters Regarding Particle Emissions

Abstract: Surface filters are widely used in industrial gas cleaning, e.g., as filter bags, to meet particle emission standards. The seam created by manufacturing the filter element is a potential leakage point for dust. A systematic investigation on the impact of the needle diameter of the seam on filter operation in two different filter test rigs is presented, regarding differential pressure and particle emissions. Four membrane samples, one without seam and three sewn with different needle diameters, were used to eva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…There are studies in the literature related to the evaluation of small coupons in filter test rigs (Bach; Schmidt, 2007; Mouret et al, 2009; Mukhopadhyay; Mahawar, 2020; Li et al, 2022), in pilot plant-scale baghouses (Mukhopadhyay; Choudhary, 2013; Kurtz; Meyer; Kasper, 2017; Bächler et al., 2020; Bächler et al, 2022), and investigation in industrial plants (Tomanovich; Knotts, 2013) that have researched the particulate emissions caused by small holes, made on purpose in the fabric, with defined diameters (pinholes), as well as the seam holes. All of these authors have concluded that the holes can greatly contribute to the overall dust emission, as presented in the work of Lacerda et al, 2022 …”
Section: Introductionmentioning
confidence: 89%
See 1 more Smart Citation
“…There are studies in the literature related to the evaluation of small coupons in filter test rigs (Bach; Schmidt, 2007; Mouret et al, 2009; Mukhopadhyay; Mahawar, 2020; Li et al, 2022), in pilot plant-scale baghouses (Mukhopadhyay; Choudhary, 2013; Kurtz; Meyer; Kasper, 2017; Bächler et al., 2020; Bächler et al, 2022), and investigation in industrial plants (Tomanovich; Knotts, 2013) that have researched the particulate emissions caused by small holes, made on purpose in the fabric, with defined diameters (pinholes), as well as the seam holes. All of these authors have concluded that the holes can greatly contribute to the overall dust emission, as presented in the work of Lacerda et al, 2022 …”
Section: Introductionmentioning
confidence: 89%
“…All of these authors have concluded that the holes can greatly contribute to the overall dust emission, as presented in the work of Lacerda et al, 2022. 11 …”
Section: Introductionmentioning
confidence: 99%
“…In the first measurement campaign (scenario 1), all filter bags were made from medium A and the seams of all but one factory-new filter bag were sealed applying a sealing paste. This creates an emission dynamic, whereby one filter bag with the regular non-sealed seams contributes greatly to the overall dust emission, as particles can easily penetrate the seams of the filter bag during the initial filtration cycles [6,14]. After several cycles, the seams are (mostly) clogged and the emission behavior approaches ideal behavior (detection of particle emission peak after filter regeneration only).…”
Section: Objective Of the Investigationsmentioning
confidence: 99%
“…or the plenum plate (incorrectly installed filter elements, missing or damaged screws, etc.) can greatly contribute to the over-all dust emission [13][14][15]. Bach and Schmidt [16] investigated the contribution of small pinhole leaks in a filter test rig and Kurtz et al [17] investigated the contribution of leaks in a small-scale baghouse filter.…”
Section: Introductionmentioning
confidence: 99%
“…Higher pulse intensities (e.g., tank pressures for filter regeneration p tank ) and shorter time durations between regenerations Δt cycle may lead to a lower differential pressure through better and more frequent cake detachment, but in turn, the consumption of pressurized air rises. Increased tank pressures are known to lead to higher dust emissions as, e.g., seams of the filter element cannot clog sufficiently and remain a source for particle penetration, but may grant a lower residual differential pressure after regeneration due to improved cake detachment [19,[22][23][24]. Klein et al [21] have shown the relevance of the efficiency of the nozzle geometries for the jet pulse and discussed the power consumption of pulse jet-cleaned filters.…”
Section: Introductionmentioning
confidence: 99%